Mechanical Properties of Self-Compacting Concrete Subjected to Elevated Temperature - Muhammad, Abubakar; M. Garba, Muhammad; Z. Abdullahi, Nafi'u; Mohammed, Musa (International Journal of Integrated Engineering, 2021)
Self-compacting concrete flows and fills reinforcement gaps and corners of formworks without the need for vibration during the pouring process. The problem associated with the production of self-compacting concreteis the use of a high dosage of cement which necessitates the addition of supplementary cementitious materials to curtail this effect. As a result, the impact of a ternary blended pozzolanic materials on the mechanical properties of SCC exposed to extreme temperatures was investigated. A quantitative research approach was employed and an experimental design method was adopted. The materials used were cement, rice husk ash, metakaolin, and pulverized burnt bricks. Laboratory tests conducted at the hardened stage were compressive strength, weight loss, and ultrasonic pulse velocity of self-compacting concretesubjected to 200°C, 400°C, 600°C, and 800°C elevated temperatures. At 800°C elevated temperature, the result of residual compressive strength shows that SCC produced withaddition of the ternary blend at 10% had a higher value of residual compressive strength of 27.3% over the control specimens. Control specimens were found to have the least values of weight loss in comparisonto the self-compacting concreteproduced with the addition of the ternary blend. The result of residual UPV shows that self-compacting concrete produced withaddition of the ternary blend at 10% had a higher value of 8.6%over the control specimens. When self-compacting concreteis to be produced with a ternary blend of rice husk ash, metakaolin, and pulverized burnt bricksand subjected to an elevated temperature of up to 800°C, 10wt.% is the optimum cement replacementlevel